Exploring the potential of assessment efficacy in sports coaching - A Commentary - Burton, D.; Gillham, A. (International Journal of Sports Science and Coaching, 2012)
For the first author who has spent 30 years conducting coaching education, Hay et al.`s provocative "call to arms" promoting assessment as a crucial tool for enhancing coaching effectiveness is clearly "preaching to the choir." The lack of systematic assessment to provide accountability and value in coaching education has been a problem for over three decades. In the early 1990`s, the first author was invited to speak about coaching evaluation to a Coaching Education Summit jointly sponsored by the United States Olympic Committee (USOC) and the American Coaching Education Program (ACEP). After an exhaustive literature review turned up no empirical research on the topic, he surveyed 20 regional high schools and 20 Northwest colleges to ask athletic directors what type of evaluation they conducted with their coaches. Except for won/loss record and parent/alumni complaints, coaching evaluation was neither based on any objective data nor conducted systematically. Thus, his talk was limited to speculating about how to evaluate coaches and suggesting three possible components to effective coach assessment, including: a) accurate identification and valid assessment of key coach competencies, b) a streamlined process that was easy to implement, and c) targeting of evaluation on formative assessment to enhance individual coaches` development. In 1992, Tom Raedeke and the first author were asked to conduct a study for ACEP to compare coaching competences for two types of formal curricula used to train high-school coaches (i.e., coaches trained through general teacher education versus nonteachers who completed ACEP coaching education). The study required development of an evaluation tool to assess coaching effectiveness, and we constructed an exploratory instrument to measure coach competencies we termed the Coaching Success Questionnaire (CSQ). Regrettably, the CSQ was not psychometrically sound enough to generate stable coach competency factors, thus making accurate evaluation of the merits of these two types of coaching training curricula virtually impossible. This experience confirmed an obvious need for a coach assessment tool, but conflicting priorities delayed the further development of the CSQ for several decades.